PENGARUH BURNOUT SYNDROME TERHADAP KINERJA PEGAWAI NEGERI SIPIL (PNS) PADA DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI JAMBI - ANISAH, ANISAH (LP2MTBM MAKARIOZ, 2023)
The aims of this study are to see the influence of burnout syndrome to the performance of Employment Service and Transmigration Jambi Province. The sample from this research uses a census method where the entire population is sampled. This research is a type of survey research, data collection techniques using a closed questionnaire given to respondents, the questions in the questionnaire were made using a Likert scale and analyzed using Simple Linier Regression. The results of the study showed that burnout syndrome have a negative and significant effect on the performance of Employment Service and Transmigration Jambi Province